2018
DOI: 10.18203/2394-6040.ijcmph20185248
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among health professionals in a tertiary medical college of northern Kerala, India

Abstract: Background: Health care has emerged as an industry with potential source of stress in the workplace environment. Burnout is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. The objectives of the study were to study proportion and associated factors of burnourt among health professionals in medical college.Methods: Data was collected using a questionnaire by using Copenhagen burnout inventory. From a sample frame from of 856, proportionate sampling was to get 187. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In contrast, no association was found in the current study. 9 The present study found that years of work experience were significantly associated with work-related burnout; the studies conducted in Delhi and Andhra Pradesh among nurses and clinicians found that respondents with low years of expertise reported high levels of burnout. 10 , 11 …”
Section: Discussionmentioning
confidence: 44%
“…In contrast, no association was found in the current study. 9 The present study found that years of work experience were significantly associated with work-related burnout; the studies conducted in Delhi and Andhra Pradesh among nurses and clinicians found that respondents with low years of expertise reported high levels of burnout. 10 , 11 …”
Section: Discussionmentioning
confidence: 44%
“…Consistent with previous studies, our results showed no significant difference between genders and burnout. 7,26,27 This may be due to the low number of male samples (14%) in this study. Therefore, samples may not be representative of gender and burnout score differences among mental health professionals.…”
Section: Discussionmentioning
confidence: 82%
“…This is a syndrome typically characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. 1 Burnout is an occupational disease is of global concern, as it affects worker's physical and mental health. Since the beginning of the COVID-19 pandemic, the HCWs had been under heavy workload conditions globally, thus leading to the increased prevalence of burnout.…”
Section: Introductionmentioning
confidence: 99%